Effect of labor dance on induction duration, first-stage labor, and maternal anxiety in pregnant women with term premature rupture of membranes: A randomized controlled trial - Zheng, Jinxuan; Wang, Biyun; Duan, Dongmei; Wu, Yingfang; Yang, Luhuan (European Publishing, 2026)
INTRODUCTION Labor dance is an emerging non-pharmacological intervention for labor support, though current evidence remains limited, especially among pregnant women with term premature rupture of membranes (TPROM). This study aims to evaluate the effect of labor dance on the duration of labor induction and the first stage of labor, as well as on maternal and neonatal outcomes and maternal anxiety.METHODS A randomized controlled trial was conducted at a tertiary maternal and child healthcare hospital in southern China from 20 November 2023 to 31 October 2024. A total of 102 eligible full-term pregnant women with premature rupture of membranes (PROM), aged 18–35 years, and primiparous with adequate health literacy and capacity for informed consent, were randomly allocated in a 1:1 ratio to either the intervention or control group. The control group received oxytocin-induction management with routine care, ambulation encouragement. The intervention group received the same care plus labor-dance sessions (8–10 minutes per sequence, at least every 30 minutes) from 0 to 5–6 cm cervical dilation. The primary outcomes measured were the duration of labor induction. Secondary outcomes included the length of the first stage of labor, maternal anxiety levels, postpartum hemorrhage within 24 hours, delivery mode, and the incidence of maternal and neonatal infections.RESULTS Compared with the control group, the intervention group had a shorter induction time (406.20 ± 177.53 vs 495.98 ± 188.22 min), with a mean difference of 89.78 minutes (95% CI: 13.99–165.57, p=0.021). Among participants who delivered vaginally, there was a shorter first stage (429.14 ± 141.39 vs 509.28 ± 167.54 min), with a mean difference of 80.14 min (95% CI: 12.59–147.68, p=0.021). Post-intervention anxiety scores were lower in the intervention group (median: 4 vs 5; p<0.05). Chorioamnionitis occurred less frequently (13.0% vs 30.4%; p<0.05). Total labor duration, 24-h postpartum hemorrhage, overall delivery mode, and neonatal complications (asphyxia/pneumonia) did not differ significantly between groups (all p>0.05).CONCLUSIONS In pregnant women with TPROM undergoing oxytocin induction, labor dance – a low-risk adjunct – was associated with shorter induction and first-stage labor, lower anxiety, and maybe reduced chorioamnionitis, without increases in postpartum hemorrhage or neonatal complications.